PENGARUH MODEL PEMBELAJARAN PROBING PROMPTING TERHADAP HASIL BELAJAR MATA PELAJARAN MATEMATIKA PADA SISWA KELAS 4 UPTD SDN BERBELUK 1 DAN 3 KABUPATEN BANGKALAN - Siti Rumiyanti; Umi Hanik (Jurnal Sosial Humaniora dan Pendidikan, 2024)
This research aims to determine the influence of learning models on student learning outcomes at UPTD SDN Berbeluk 1 and 3, Arosbaya Bangkalan sub-district. The method used is a quantitative research method. The type of research used in this research is experimental research using a pre-experimental design type of research with a one group pre test-post test design type. Based on the data processing carried out, it is known that there is an influence of the probing prompting learning method on mathematics learning outcomes in grade 4 students at UPTD SDN Berbeluk 1 and 3, Bangkalan Regency. This is indicated by a significant value of 0.000 > 0.005 so that the hypothesis decision is accepted, which means that there is an influence of providing the probing prompting learning method on mathematics learning outcomes in grade 4 students. Based on the results of research regarding the influence of the Probing prompting learning model on mathematics learning outcomes in grade 4 students at UPTD SD In terms of 1 and 3, Bangkalan district for the 2023-2024 academic year, it can be concluded that the Probing prompting learning model influences the mathematics learning outcomes of grade 4 UPTD SDN students in areas 1 and 3.